2001
DOI: 10.1039/b007495k
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the equation of state and the surface tension of water-soluble polymers: poly(ethylene glycol)-b-poly(propylene glycol)-b-poly(ethylene glycol) + water at 298.15 K

Abstract: The equation of state of poly(ethylene glycol)-b-poly(propylene glycol)-b-poly(ethylene glycol) (PEGÈPPGÈPEG) ] water has been measured in the sol phase at 298.15 K and up to 40 MPa. For the sake of comparison two mixtures of (PEG ] PPG) ] water, with the same PEG : PPG ratio as the copolymer, have been measured. The di †erences found between the data of the copolymer and the blend solutions are well beyond the experimental precision, the compressibility for the copolymer mixtures being larger than for the ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…For water, ℓ c ≈ 2 mm, while for aqueous PEG solutions such as ours the surface tension can be a factor of two smaller over a wide range of concentrations with similar density, making the capillary length shorter but still of roughly millimetre length 43 . The overpressure in the film, Δ p , is coupled to the volume of the fluid surrounding the nanoparticle, and is determined by the formation process of the liquid nanolenses.…”
mentioning
confidence: 83%
“…For water, ℓ c ≈ 2 mm, while for aqueous PEG solutions such as ours the surface tension can be a factor of two smaller over a wide range of concentrations with similar density, making the capillary length shorter but still of roughly millimetre length 43 . The overpressure in the film, Δ p , is coupled to the volume of the fluid surrounding the nanoparticle, and is determined by the formation process of the liquid nanolenses.…”
mentioning
confidence: 83%
“…Very dilute mixtures have been included in this study because strong surface tension reductions are observed in that composition range, and correlations between γ and P-V-T data have been reported. 12 As it can be observed, the effect of pressure on the molar volume is lower for the mixtures richer in the component that can form a denser hydrogen-bond network (1,4- However, this cannot be taken as a general result, since V/V 0 shows a smaller pressure dependence for water than for 1,4-butanediol.…”
Section: Resultsmentioning
confidence: 97%
“…To evaluate the F cav and F solv components in eq 4 and to estimate Δ G elec in eq 5, the surface tension and the dielectric constant of the solvent are required. These constants are summarized in Table . , As reference compounds, we used n -butylamine ( n -BuNH 2 ) for lysine, ethylamine for diaminobutyric acid, and propylamine for the ornithine side chain, respectively. Their p K a values in water, methanol, 95% methanol/5% water mixture, and DMSO are listed in Table . ,,, …”
Section: Methodsmentioning
confidence: 99%